To simplify the expression (-47) - 33 ÷ (-3) - 3 × (-7), use the order of operations (PEMDAS/BODMAS) to calculate step by step. The simplified expression is -15.
To simplify the expression (-47) - 33 ÷ (-3) - 3 × (-7), we need to follow the order of operations (PEMDAS/BODMAS).
PEMDAS stands for Parentheses, Exponents, Multiplication and Division (from left to right), and Addition and Subtraction (from left to right).
Therefore, the simplified expression is -15.
#SPJ2
The length of the third side is 3.6 units
Let the sides of the triangle be;
x, y and z
So, we have:
x = 3
y = 4
<Z = 60
The length of the third side is then calculated using the following law of cosine
z^2 = x^2 + y^2 - 2xy cos(Z)
So, we have:
z^2 = 3^2 + 4^2 - 2 * 3 * 4 * cos(60)
Evaluate the exponents and the product
z^2 = 9 + 16 - 12
Evaluate the sum and the difference
z^2 = 13
Take the square root of both sides
z = 3.6
Hence, the length of the third side is 3.6 units
Read more about law of cosines at
#SPJ5
Answer:
13
Step-by-step explanation:
∠Q ≅ ∠ P ⇒ RP = RQ = 13
Answer:$40
Step-by-step explanation:
5x2(____) − 2(____)
What is the common factor that is missing from both sets of parentheses?
−2x − 7
2x + 7
−2x2 + 7
2x2 + 7
The common factor that is missing from both sets of parentheses is 2x + 7
To determine the missing factor, we would divide 10x³ + 35x² − 4x− 14 by 5x² – 2 using long division method as illustrated below
2x + 7
5x² – 2|10x³ + 35x² − 4x − 14
–(10x³ – 4x)
35x² – 14
–(35x² – 14)
0
The result obtained from the division is 2x + 7.
Therefore, the missing factor is 2x + 7
(5x² – 2)(2x + 7) = 5x²(2x + 7) – 2(2x + 7)
Learn more about polynomial:
i believe the correct ones are...
1
3
5
7